PENGEMBANGAN BAHAN AJAR MEDIA PEMBELAJARAN MATEMATIKA BERBASIS LECTORA INSPIRE DI SEKOLAH DASAR - Ika Rostika; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah (Universitas Pendidikan Indonesia, 2020)
This research aims to develop teaching materials for mathematics learning media based on lectora inspire in elementary schools on the material of plane properties, to see the response and understanding of students. The subject of this study was the fifth grade students of SDN Pasir. Amounting to 30 students in the 2018/2019 academic year. Data collection is obtained by tests, questionnaires and documentation. The results of the study were (1) obtained an average score of expert validation of 84.15% with the category